2011
DOI: 10.1099/jmm.0.030163-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two commercial molecular tests for the detection of Clostridium difficile in the routine diagnostic laboratory

Abstract: Two commercial real-time PCR assays for the detection of Clostridium difficile, BD GeneOhm Cdiff assay (BD Diagnostics) and Xpert C. difficile assay (Cepheid), were compared to each other and to toxigenic culture, which was used as a gold standard, on a set of 194 clinical stools submitted for routine diagnostic analysis. Of 28 (14.4 %) toxigenic culture positive samples 23 were positive with both assays, the BD and the Cepheid real-time PCR assays, 4 were positive only by Cepheid Xpert C. difficile assay and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…The superscript b after GenϪ/Xpϩ (4.9%) indicates that one culture-positive specimen had a borderline result using the GenomEra C. difficile assay both on the first test and on retest; therefore, the final molecular result was considered negative. (10,15,(17)(18)(19)(20)(21)(22)(23)(24)(25), we found only 1 study evaluating it with the same algorithm as ours and using toxigenic culture as the gold standard (15). The authors found that the Se, Sp, PPV, and NPV of the algorithm were 86.1%, 97.8%, 88.6%, and 97.2%, respectively.…”
mentioning
confidence: 89%
“…The superscript b after GenϪ/Xpϩ (4.9%) indicates that one culture-positive specimen had a borderline result using the GenomEra C. difficile assay both on the first test and on retest; therefore, the final molecular result was considered negative. (10,15,(17)(18)(19)(20)(21)(22)(23)(24)(25), we found only 1 study evaluating it with the same algorithm as ours and using toxigenic culture as the gold standard (15). The authors found that the Se, Sp, PPV, and NPV of the algorithm were 86.1%, 97.8%, 88.6%, and 97.2%, respectively.…”
mentioning
confidence: 89%
“…LAMP was used for diagnostic purposes in all the studies and not for screening patients. The quality of studies as assessed by the QUADAS-2 tool was generally high, with all but one study [35] meeting 6 or more of the criteria (Supplementary figure 1A and 1B). Three studies [28,36,37] used CCNA as a reference test.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…After reviewing the titles and abstracts, 21 articles were selected for full-text evaluation (Figure 1). Sixteen articles with 18 studies published between 2005 and 2014 reported the sensitivity and specificity of LAMP on stool samples for the diagnosis of C. difficile infection, and were included in our meta-analysis [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Five articles were excluded (reasons for exclusion in Figure 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…With regard to false negatives, two patients tested positive just hours after the initial negative test, which is strongly suggestive of false-negative results, especially since both of these patients had clinical evidence of C. difficile-associated diarrhea. Prior studies have shown the Cepheid Xpert C. difficile PCR assay to have a sensitivity of 96 to 97% (8)(9)(10)(11), so a significant number of false negatives should be expected in a laboratory that performs thousands of tests annually; the overall prevalence of CDI for inpatients at New York-Presbyterian Hospital, Columbia University Medical Center (NYPH/CUMC) was 1.6% in the year 2013. Furthermore, many patients with suspected CDI receive empirical antimicrobial therapy prior to stool sample collection, which can potentially lead to an increased rate of false-negative results.…”
Section: Discussionmentioning
confidence: 99%